POP UP BOOK “AYO KE PURA”: MEDIA KOMUNIKASI ORANGTUA DALAM PROSES PENGENALAN AGAMA PADA ANAK USIA DINI - Ni Putu Sasmika Dewi (IAHN Gde Pudja Mataram, 2022)
Communication media is a means of communication that can be in the form of tools or facilities used by communicators to convey information or messages to many people. Pop up book is one of the communication media in the form of print. The Pop Up Book here is in the form of a book which is contains moving parts or has 3D elements and is able to provide a visualization element of the story in it to make it more interesting. This article aims to find out the use of the “Ayo Ke Pura” pop up book as a communication medium for parents in the process of introducing religion to early childhood. This research was conducted by using a descriptive qualitative approach. The results of this study are that children respond well and enthusiastically when their parents teach religious knowledge with the pop up book communication media, establishing a good two-way communication system between parents and children when carrying out the process of introducing religion using pop up books.